Perpaduan Aspek Sosial-Budaya Melayu Dan Jawa Pada Kehidupan Ekonomi Masyarakat Nelayan Tradisional - Irawan Fakhrudin Mahalizikri (LPPM ISNJ Bengkalis, 2016)
Boeke probably not the first to fully conduct studies on dimensional-culture in economic activity in rural communities traditional refer to as